Occurrence, sources, and ecological risk of polycyclic aromatic hydrocarbons (PAHs) in rice field soils of northwestern Peru - Culqui Gaslac, Cristian (2026)
Polycyclic aromatic hydrocarbons (PAHs) are organic contaminants that pose significant risks to human health and ecosystems. This study investigated the occurrence, sources, and ecological risks of PAHs in rice paddy soils from northwestern Peru. Ninety-seven soil samples were collected at a depth of 30 cm across three altitudinal zones, four phenological stages, and two agronomic management practices. Quantification was performed using ultra-high-performance liquid chromatography coupled with fluorescence detection (UHPLC-FLD). Source apportionment was conducted through rotated principal component analysis combined with multiple linear regression. Ecological risk was assessed using organic carbon normalization and the mean effects range-median quotient (M-ERM-Q) method, while carcinogenic potential was estimated using the toxic equivalent factor (TEQCARC). Total PAHs ranged from 22.02 to 130.55 ng g⁻¹ (mean: 55.26 ng g⁻¹); LMW PAHs averaged 37.38 ng g⁻¹, exceeding HMW PAHs (17.88 ng g⁻¹). No significant differences were observed among altitudinal zones, phenological stages or agronomic practices (p > 0.05). The predominant sources of PAHs were attributed to vehicular emissions (52.3%), petroleum and biomass combustion (42.1%), and coal combustion (5.4%). Ecological risk assessment revealed low contamination levels below established safety thresholds (CEC <290 μg g⁻¹), consistent with the carcinogenic risk estimated through TEQCARC (0.0083 to 18.7483 ng BaPeq g⁻¹). This study provides the first comprehensive evaluation of PAHs contamination in rice paddy soils in Peru and underscores the influence of altitude and agricultural practices, emphasizing the need for further research on pollution sources, impacts on crop productivity, and potential risks to human health.